Kronos: Southern African Histories - Hayes, Patricia (Kronos: Southern African Histories, 2017)
Since 4 May 1978, the day It was attacked by the South African Defence Force, the SWAPO camp at Cassinga, Angola, has been a key site in the national history of Namibia. The cover photograph for this issue of Kronos was taken at Cassinga on 3 May 1978, the day before the South African attack. Thereafter, the photograph was reproduced in publications by SWAPO and its allies alongside descriptions of the brutal raid on Namibian ’refugees’. The photograph is more than an Image of anonymous, now dead refugees, however. It depicts people living at Casslnga, participating in a parade held in honour of two Swedish journalists responsible for taking the picture. As Christian Williams argues in his contribution to this Issue, photographs such as this one have obscured the community of people who lived at Cassinga by rendering It either as a ’refugee’ or as a ’military’ camp. Nevertheless, as Williams suggests, this photograph also has the potential to illuminate people whose histories have been overdetermined by a dominant national narrative.